Single-Use versus Reusable Gastroscopes for the initial Assessment of patients with Upper Gastrointestinal Bleeding: A Prospective Randomised Non-Inferiority Trial - Römmele, Christoph; Ayoub, Mousa; Scheppach, Markus Wolfgang; Muzalyova, Anna; Wanzl, Julia; Tadic, Vidan; Braun, Georg; Weber, Tobias; Roser, David; Nagl, Sandra; Messmann, Helmut; Ebigbo, Alanna (Endoscopy)
Background and study aims: Recently, several single-use endoscopes have been developed. However, clinical performance remains unclear. This trial aims to compare the performance of single-use gastroscopes (SUG) with that of reusable gastroscopes (RUG), in the context of emergency esophagogastroduodenoscopy (EGD) for suspected upper gastrointestinal bleeding (UGIB). Patients and methods: Patients with suspected UGIB requiring EGD between March 2023 and April 2024 were randomized, one of which received EGD with a SUG, the other with a RUG. The primary outcome was the complete assessment of the upper gastrointestinal tract (UGIT) for the presence of a bleeding site. Results: 148 patients were included between 03/2023 and 04/2024. A complete assessment of the UGIT was achieved in 72 of 74 patients with the SUG and in 71 of 74 patients with the RUG, (97.3% vs. 95.9%; p<0.001), however, the bleeding site was identified significantly more frequently in the reusable group (83.8% vs. 68.9%, p=0.033). The need for a therapeutic intervention did not differ between the groups (55.4% vs. 50.0%, p=0.510). Five crossovers to a RUG occurred, largely due to better visualization and user experience. Conclusions: SUG are non-inferior to RUG in the complete assessment of the UGIT in patients with signs of upper GIB, however, a significantly higher rate of bleeding site identification, superior visualization quality, greater acceptance by endoscopists, and a trend toward more effective therapeutic performance was achieved with RUG.